Primaquine decreased plasma concentration of ritonavir: single- and repeated-dose study in Sprague Dawley rats (Faculty of Medicine Universitas Indonesia, 2011)
Background: The present study was aimed to explore the effects of ritonavir and primaquine combination given as a singledose or repeated-dose compared to ritonavir alone on ritonavir plasma concentration in the rats. Methods: In single-dose study, 30 male Spraque Dawley rats were randomly allocated to receive ritonavir 20 mg/kg BW or ritonavir 20 mg/kg BW + primaquine 1.2 mg/kg BW or ritonavir 20 mg/kg BW + ketokonazole 10 mg/kg BW. Ketokonazole was used as positive control of ritonavir metabolism inhibitor. In the repeated-dose study, thirty Spraque Dawley male rats were randomly allocated to receive ritonavir 20 mg/kg BW/day or ritonavir 20 mg/kg BW/day + primaquine 1.2 mg/kg BW/day or ritonavir 20 mg/kg BW/day + rifampicin 100 mg/kg BW/day. Rifampicin was used as a positive control of ritonavir metabolism inducer. Results: In the single-dose study, ketokonazole increased the area under the plasma concentration (AUC) of ritonavir (↑114.8%, p< 0.05), while primaquine tended to decrease the AUC of ritonavir (↓32.6%, p> 0.05). Repeated-dose study showed that rifampicin decreases the AUC of ritonavir (↓42.8%, p< 0.001), and primaquine decreased the AUC of ritonavir plasma concentration (↓46.6%, p< 0.001). Conclusion: Concomitant administration of primaquine and ritonavir decreases the AUC of ritonavir. This effect may result in the insufficient concentration of ritonavir as anti-HIV, which may lead to treatment failure with ritonavir. (Med J Indones 2011; 20:190-4)